Analisis Strategi Pemasaran Priority Banking Officer (PBO) Dalam Meningkatkan Jumlah Nasabah Prioritas Pada PT Bank Syariah Indonesia (KCP. Perbaungan) - Fitriyani Fitriyani; Tuti Anggraini (ITB AAS INDONESIA Surakarta, 2023)
This research was written to find out the strategies used to increase priority customers at PT. Bank Syariah Indonesia Kcp Perbaungan. This study aims to look at the strategies, constraints, and their impact on increasing the number of priority customers. This type of research is a descriptive-qualitative method that focuses on in-depth observations, namely universal descriptions of form, function and meaning. The source of this research is the results of interviews with Priority Banking Officer staff of PT. Bank Syariah Indonesia, which contains strategies and constraints on the marketing strategy. The research results obtained by the author are the marketing strategy carried out by Priority Banking Officer staff, namely carrying out a marketing mix strategy in the form of approaching customers who have criteria as priority customers, namely one of them has a minimum balance of Rp. 500 million, conducting word-of-mouth promotions, as well as promoting on social media, providing more special services than non-priority customers, regardless of race or creed and providing facilities to customers. The obstacle faced is competition between banks. The way to minimize obstacles is to approach, stay in touch, and provide education to customers. The strategy carried out has proven to have an effect on increasing the number of priority customers, it can be seen that in August and October 2022 there was an increase in the number of customers which was in line with the development of PT. Bank Syariah Indonesia, namely the number of priority customers, increased by 17.9% as of August compared to the previous period with a range of more than 50 thousand priority customers throughout Indonesia.